The Study of Staging in 3D Animated Film in Malaysia - A Samad, Ahmad Ridhwan; Abdul Ghani, Dahlan (Journal of Computing Technologies and Creative Content, 2017)
Animation is an animated movement through the frames using paper or digital by hand. In Malaysia, they still have a lot to improve with their animation to attract the audience to watch the animation. The purpose of this research is to study the values and importance of staging in developing 3D animated films in Malaysia. In order to make the narrative or character pose or action should clearly communicate to the audience the attitude, mood, reaction or idea of the character as it relates to the story and continuity of the story line. The effective use of long, medium, or close up shots, as well as camera angles also helps in telling the story. Applying the art of “staging” within the 12 principles of animation founded by Disney, can be used to get the best result in animation. Also in this research, the methodology used in this research will focus on observation and literature review studies. Staging directs the audience’s attention to the story or idea being told. With this research, it will provide a benefit to other animators that can use the info that is present in this research for improving their understanding in animation.